Molecular detection of rickettsial agents of hard ticks (Acari: Ixodidae) collected from wild birds of Panama - Bermúdez, Sergio (2020)
Instituto Conmemorativo Gorgas de Estudios de la Salud. Departamento de Investigación en Entomología Médica. Panamá / Estación Científica Coiba AIP, Panamá.